Mediator-Less Electrocatalytic Oxidation of NADH at Oxygen Plasma Treated Screen Printed Carbon Electrodes. (19th September 2015) - Mutyala, Sankararao; Mathiyarasu, Jayaraman
Abstract : Here in, we report a simple and sensitive method for NADH determination using oxygen plasma treated screen printed carbon electrode (OPSPCE) without employing redox mediator. The OPSPCE is more electroactive toward NADH oxidation, which is envisaged with decrease in overpotential of ∼130 mV and increase in oxidation current compared to SPCE. The activity improvement is reasoned as generation of oxygen functionalities along with creation of edge plane sites during oxygen plasma treatment. This was confirmed by Fourier transform infra-red (FT-IR) and Raman spectroscopic studies. Using OPSPCE, NADH quantification was demonstrated for a concentration range 3 - 27 μM with 0.6 μM LOD.